2010
DOI: 10.3945/jn.110.128330
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of the Human Ortholog of Riboflavin Transporter 2 and Riboflavin-Responsive Expression of Its Rat Ortholog in the Small Intestine Indicate Its Involvement in Riboflavin Absorption , ,

Abstract: Riboflavin transporter (RFT) 2 has recently been identified as a transporter that may be, mainly based on the functional characteristics of its rat ortholog (rRFT2), involved in the intestinal absorption of riboflavin. The present study was conducted to further examine such a possible role of RFT2, focusing on the functional characteristics of its human ortholog (hRFT2) and the response of rRFT2 expression in the small intestine to deprivation of dietary riboflavin. When transiently expressed in human embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 21 publications
5
50
0
Order By: Relevance
“…The riboflavin contents in the control and deficient diet were 6.5070.42 and 0.3070.05 mg/kg, respectively. The composition of the AIM-93M diet has been reported previously (Fujimura et al, 2010).…”
Section: Riboflavin Deprivation In Micementioning
confidence: 99%
“…The riboflavin contents in the control and deficient diet were 6.5070.42 and 0.3070.05 mg/kg, respectively. The composition of the AIM-93M diet has been reported previously (Fujimura et al, 2010).…”
Section: Riboflavin Deprivation In Micementioning
confidence: 99%
“…The protein is believed to play an important role in intestinal riboflavin absorption [2,3]. Riboflavin deficiency has been shown to be an important risk factor for ESCC [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have investigated the relationship between riboflavin and intestinal health of fish. In human and rats, the intestine has developed riboflavin transporter to transport and absorb riboflavin [6]. Meanwhile, it was reported that dietary riboflavin deficiency could reduce iron absorption and increase gastrointestinal iron loss in rats [7].…”
Section: Introductionmentioning
confidence: 99%